Investigation of Sliding Wear Behaviour of HVOF Carbide Coating. (2018) - Kishore Mishra, Tribhuwan; Kumar, Arbind; Sinha, SK; Sharma, Satpal
Abstract: In this Present work dry sliding wear tests on specimens of Mild Steel, WC-12Co and WC-10Co-4Cr coated specimens were performed against a hardened EN32 steel disc under dry sliding conditions. High Velocity Oxy-Fuel flame spraying technique (HVOF) was used to deposit the coating on 1020 grade steel then theses coated sample characterized using scanning electron microscopy, X-ray diffraction (XRD), coefficient of friction (COF), hardness The experiment result show MS specimen suffered high wear loss, but the WC-Co and WC-Co-Cr specimen showed negative wear and higher friction coefficient .Hardness is higher in the WC-12Co coating than in the WC-10Co-4Cr coating. The SEM image shows the bright and dark grey regions corresponding to tungsten carbide and cobalt binder phase XRD result shows that decomposition of WC (into W2 C and W) cases lower wear